2018
DOI: 10.1016/j.jelekin.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vibration-induced fatigue on the H-reflex

Abstract: Vibration exercise (VE) has been suggested as an effective training for improving muscle strength and coordination. However, the underlying physiological adaptation processes are not yet fully understood, limiting the development of safe and effective exercise protocols. To better understand the neuromuscular responses elicited by VE, we aimed at investigating the acute effects of superimposed vibration on the Hoffmann reflex (H-reflex), measured after fatiguing exercise. Twenty-five volunteers performed four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Previous studies reported increased sEMG RMS during VE (Bosco et al 1999, Roelants et al 2006, and others have shown estimates of global sEMG features during vibration (Xu et al 2016b, Sammali et al 2018. However, there are no previous studies that assessed MU recruitment by mCV analysis during vibration.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies reported increased sEMG RMS during VE (Bosco et al 1999, Roelants et al 2006, and others have shown estimates of global sEMG features during vibration (Xu et al 2016b, Sammali et al 2018. However, there are no previous studies that assessed MU recruitment by mCV analysis during vibration.…”
Section: Introductionmentioning
confidence: 98%
“…Conversely, a decrease in the EMG–power ratio after the WBV intervention was observed in our study; this result highlights an improved neuromechanical efficiency at submaximal loads that largely reflects the activity of high-threshold motor units 65 and results from a combination of 2 mechanisms. First, fatigue-induced reflex inhibition of the motoneuron pool excitability after WBV 66 could contribute to a reduction in the neural drive of agonist-antagonist thigh muscles (ie, the “numerator” of the EMG-power ratio); this peripheral inhibition could also explain the fatigue due to central components (central–peripheral interactions) as evidenced by the significant reduction in MIVC in the present study. In fact, when the discharge frequency of motoneurons declines toward low values, following the altered afferents induced by stretch-shorten cycles of WBV, 66 a higher central activation rate, through supraspinal projections of afferents, is delivered to motor units to exert the same relative level of strength; in this way, the central motor commands force the recruitment of new motor units, and central fatigue must appear in the task when the muscles work closest to their maximal levels.…”
Section: Discussionmentioning
confidence: 73%
“…First, fatigue-induced reflex inhibition of the motoneuron pool excitability after WBV 66 could contribute to a reduction in the neural drive of agonist-antagonist thigh muscles (ie, the “numerator” of the EMG-power ratio); this peripheral inhibition could also explain the fatigue due to central components (central–peripheral interactions) as evidenced by the significant reduction in MIVC in the present study. In fact, when the discharge frequency of motoneurons declines toward low values, following the altered afferents induced by stretch-shorten cycles of WBV, 66 a higher central activation rate, through supraspinal projections of afferents, is delivered to motor units to exert the same relative level of strength; in this way, the central motor commands force the recruitment of new motor units, and central fatigue must appear in the task when the muscles work closest to their maximal levels. 67 In this regard, the MIVCs decreased significantly in both groups, but only in the WBV intervention did EMG activity and the EMG-MIVC ratio show an increasing trend (although not significant).…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, our protocol may have been too short to induce acute changes in the spinal circuitry function in MS patients compared to healthy individuals. Nevertheless, with long-term intervention protocols, the effect of muscle fatigue on H-reflex should be taken into account, as muscle fatigue reduces Ia-afferent excitation or increases nerve fiber excitability thresholds [87]. In this regard, we can state that muscle fatigue did not occur as MVIC values did not change between baseline levels and those measured at the end of the entire protocol in both MS and CG [39,49,56].…”
Section: Discussionmentioning
confidence: 96%